Sales, Short-Term Debt, Long-Term Debt, and Net Profit: A Study of Companies in Jakarta Islamic Index (JII) - Nurwani Nurwani; Laylan Syafina (Trunojoyo University of Madura, 2022)
ABSTRACTThis study examines and analyzes the effect of sales, short-term debt, and long-term debt on net profit.The population of this research is the financial statements of the Jakarta Islamic Index (JII) companies for the 2018-2020 period as many as 30 companies and the sample is 28 companies using purposive sampling technique. The data analysis technique used multiple linear regression analysis, hypothesis testing, and determination test. The results show that sales and short-term debt have a positive and significant effect on net profit partially, while long-term debt has a positive and significant effect on net profit. Finally, the results of the research are sales, short-term debt, and long-term debt have a significant effect on net profit.